2018
DOI: 10.3390/ijgi7110445
|View full text |Cite
|
Sign up to set email alerts
|

Species-Level Vegetation Mapping in a Himalayan Treeline Ecotone Using Unmanned Aerial System (UAS) Imagery

Abstract: Understanding ecological patterns and response to climate change requires unbiased data on species distribution. This can be challenging, especially in biodiverse but extreme environments like the Himalaya. This study presents the results of the first ever application of Unmanned Aerial Systems (UAS) imagery for species-level mapping of vegetation in the Himalaya following a hierarchical Geographic Object Based Image Analysis (GEOBIA) method. The first level of classification separated green vegetated objects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…Only one of their examples involved census of a rare species, Caicos pine, within an area. The few species successfully quantified with drone imagery have usually been trees [15][16][17][18]. Drones have been successfully used to map herbaceous invasive species infestations, but the species mapped are usually clonal species that can be quantified using vegetation mapping techniques; efforts to map invasive species individuals intermingled in other vegetation have been less successful [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Only one of their examples involved census of a rare species, Caicos pine, within an area. The few species successfully quantified with drone imagery have usually been trees [15][16][17][18]. Drones have been successfully used to map herbaceous invasive species infestations, but the species mapped are usually clonal species that can be quantified using vegetation mapping techniques; efforts to map invasive species individuals intermingled in other vegetation have been less successful [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the OBIA methods are widely applied in multi-scale research [15,16], change detection [17] and landslide detection [18]. To better understand ecological patterns, it is also expanded to the species-level mapping of vegetation [19]. Other research, like References [20,21], presented a comparative evaluation of the pixel-based method and the object-based; especially, Reference [21] compared the pixel-based support vector machine (SVM) classification and decision-tree-oriented geographic object-based image analysis (GEOBIA) classification, which indicated that the GEOBIA classification provided the highest accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Figure19. The classification results and the object masks in sample V. The yellow box presents the forest 1 object that will be analyzed in this section, and the red box presents the misclassified result.…”
mentioning
confidence: 99%
“…For example, Hodgson et al (2018) found that counting the number of seabirds within colonies was more accurate when automated though UAV imagery than with trained field technicians. Mishra et al (2018) tested the ability to identify individual tree species along a tree line ecotone in Nepal and found approximately 70% accuracy using UAV imagery alone. Grassland applications have largely been limited to quantifying the presence of a single species, landcover and vegetation types, biomass, and disturbances such as prescribed burns (Zweig et al 2015; Cruzan et al 2016; Lorah 2018; Lussem et al 2019; Melville et al 2019).…”
Section: Introductionmentioning
confidence: 99%